METODOLOGI TAFSIR AL-QUR’AN: MASA KLASIK HINGGA KONTENPORER - Darul, Muhammad Ghalib (LPPM STAI Muhammadiyah Probolinggo, 2025)
This paper explores the development of Qur’anic exegesis methodology from the classical to the contemporary period using a qualitative library research approach. The study aims to identify the various interpretive methods employed by Qur’anic scholars (mufassir) throughout history, as well as their significance in preserving the integrity of divine revelation and addressing the demands of changing times. Qur’anic interpretation requires a robust methodological foundation to avoid misinterpretation. Historically, methods such as bi al-ma’tsur (transmitted), bi al-ra’yi (reason-based), ijmali (general), tahlili (analytical), maudhu’i (thematic), and muqaran (comparative) have evolved to suit different socio-religious contexts. In the modern era, new approaches like contextual, maqasidi, and scientific interpretations have emerged in response to contemporary issues such as environmentalism, gender, and pluralism. This study also highlights the importance of mastering auxiliary sciences such as Arabic grammar, rhetoric, and the reasons for revelation (asbab al-nuzul) as prerequisites for valid interpretation. Thus, the methodology of tafsir is not merely an academic tool but a spiritual framework ensuring that the divine message of the Qur’an remains authentic, relevant, and applicable across time and context.